Recent Results on Robust Estimation in Multivariate Analysis (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
Classic methods in multivariate analysis require the estimat.ion of mean vectors and covariance matrices, and their results can therefore be substantially altered by a small proportion of atypical observations ( "outliers").